Prosocial Behavior of Students Using Social Media - Lailatul Chasanah; Effy Wardati Maryam (Universitas Muhammadiyah Sidoarjo, 2022)
This research is motivated by the existence of prosocial behavior problems in students who use social media. This study aims to describe the prosocial behavior of students using social media at Muhammadiyah University of Sidoarjo quantitatively descriptively. The population in this study were all active students of Muhammadiyah University of Sidoarjo as many as 9943 people. The sample used is 335 people based on an error rate of 5% in the table developed by Isaac and Michael. The sampling technique used in this study is a convenience sampling technique. The data collection technique in this study used a psychological scale, namely the prosocial behavior scale in the form of a Likert scale. The result of the reliability test is 0.894. The results showed that the prosocial behavior of students using social media at Muhammadiyah University of Sidoarjo was mostly in the moderate category (64.2%) and less than half in the high category (20.3%) and in the low category (15.5%). This means that students who use social media are able to carry out prosocial behavior that can benefit and change the physical and psychological conditions of other individuals without having to get a direct benefit.